CD4+ and CD8+ T‐Cell‐Specific DNA Cytosine Methylation Differences Associated With Obesity. Issue 8 (28th June 2018) - Hohos, Natalie M.; Smith, Alicia K.; Kilaru, Varun; Park, Hea Jin; Hausman, Dorothy B.; Bailey, Lynn B.; Lewis, Richard D.; Phillips, Bradley G.; Meagher, Richard B.
Abstract : Objective: Lifestyle factors associated with obesity may alter epigenome‐regulated gene expression. Most studies examining epigenetic changes in obesity have analyzed DNA 5´‐methylcytosine (5mC) in whole blood, representing a weighted average of several distantly related and regulated leukocyte classes. To examine leukocyte‐specific differences associated with obesity, a pilot study examining 5mC in three distinct leukocyte types isolated from peripheral blood of women with normal weight and obesity was conducted. Methods: CD4 + T cells, CD8 + T cells, and CD16 + neutrophils were reiteratively isolated from blood, and 5mC levels were measured across >450, 000 CG sites. Results: Nineteen CG sites were differentially methylated between women with obesity and with normal weight in CD4 + cells, 16 CG sites in CD8 + cells, and 0 CG sites in CD16 + neutrophils (q < 0.05). There were no common differentially methylated sites between the T‐cell types. The amount of visceral adipose tissue was strongly associated with the methylation level of 79 CG sites in CD4 + cells, including 4 CG sites in CLSTN1 's promoter, which, this study shows, may regulate its expression. Conclusions: The methylomes of various leukocytes respond differently to obesity and levels of visceral adipose tissue. Highly significant differentially methylated sites in CD4 + and CD8 + cells in women with obesity that have apparent biological relevance to obesity were identified.